2015
DOI: 10.1007/s11356-015-4273-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between bacterial energetic metabolism, mercury methylation potential, and hgcA/hgcB gene expression in Desulfovibrio dechloroacetivorans BerOc1

Abstract: The proteins encoded by the hgcA and hgcB genes are currently the only ones known to be involved in the mercury methylation by anaerobic microorganisms. However, no studies have been published to determine the relationships between their expression level and the net/gross methylmercury production. This study aimed to decipher the effect of growth conditions on methylmercury production and the relationships between hgcA and hgcB expression levels and net methylation. Desulfovibrio dechloroacetivorans strain Ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 37 publications
9
67
0
Order By: Relevance
“…Only seven proteins showed a greater than twofold change in differential abundance (Table S2, Supporting Information). These results thus indicate that Hg did not induce substantial changes in the expression levels of either HgcA or HgcB, consistent with previous observations . For example, in short‐term incubation (1 h) experiments with the sulfate‐reducing bacterium Desulfovibrio dechloroacetivorans BerOc1, Goni‐Urriza and colleagues reported no significant induction of hgcA and hgcB genes by inorganic Hg .…”
Section: Resultssupporting
confidence: 90%
“…Only seven proteins showed a greater than twofold change in differential abundance (Table S2, Supporting Information). These results thus indicate that Hg did not induce substantial changes in the expression levels of either HgcA or HgcB, consistent with previous observations . For example, in short‐term incubation (1 h) experiments with the sulfate‐reducing bacterium Desulfovibrio dechloroacetivorans BerOc1, Goni‐Urriza and colleagues reported no significant induction of hgcA and hgcB genes by inorganic Hg .…”
Section: Resultssupporting
confidence: 90%
“…The bacterial ability to methylate Hg has been shown to depend on the presence of the hgcAB gene cluster in the laboratory (Gilmour et al 2013;Parks et al 2013), but the fact that the concentration of MeHg in environmental samples is the net result of (i) formation (Hg methylation), (ii) degradation (MeHg demethylation), and (iii) Hg 2+ reduction to Hg 0 Environ Sci Pollut Res could explain the lack of obvious correlation between the gene expression level and the MeHg concentration. However, this observation was also in agreement with a recent laboratory study showing a poor correlation of hgcAB expression level with net Hg methylation (Goni-Urriza et al 2015). Furthermore, in the present study, the abundance of the hgcA transcript correlated with the OM in the surface sediments (0-1 cm), suggesting that the expression of this gene depends rather on OM available for the activity of the heterotrophic Hg-methylating bacteria.…”
Section: Discussion Dispersion and Fate Of Hg In Downstream Reservoirssupporting
confidence: 93%
“…In another example of the use of molecular techniques it was observed that the greater relative abundance of organisms with known methylator gene sequences in the sediment microbiome of high carbon DOM, as opposed to oligotrophic, mesocosms (Graham et al in review). Goñi-Urriza et al (2015) showed that hgcAB gene expression varied in Desulfovibrio dechloroacetivorans BerOc1 when grown under sulidogenic conditions and different carbon sources. However, they were unable to relate gene expression to potential methylation rates.…”
Section: How Do We Deal With So Many Confounding Factors?mentioning
confidence: 99%